TOWARDS THE INSTITUTIONALIZATION OF PARLIAMENTARY TECHNOLOGY ASSESSMENT: THE CASE FOR IRELAND. Issue 3 (19th August 2014) - Csaki, Csaba; Fitzgerald, Ciara; O'Raghallaigh, Paidi; Adam, Frederic
Abstract : Purpose: With emphasis on innovation and knowledge-based economies society faces a proliferation of technological challenges with far-reaching, unpredictable impacts. Elected representatives need unbiased scientific knowledge to underpin evidence-based policy decision making. Parliamentary Technology Assessment (PTA) is directed at policy-oriented decision-making processes within the parliament. This paper considers the case study of Ireland with regards to the implementation of a formal PTA capability. It identifies the role played by existing agencies and the gaps that remain to be filled in the current landscape. It explores the feasibility of potential future institutional arrangements in a country without a recognised formal PTA agency. Design/methodology/approach: An embedded case study approach was utilized based on three main sources of evidence: relevant published documents pertaining to science and technology governance; interviews with key decision makers; and illustrative case of 'hydraulic fracking' demonstrating key issues stemming from the lack of a formal PTA structure. Findings: The case revealed the interplay between key actors in the area of science, technology and innovation in Ireland. It demonstrated the need for improved citizen engagement. The analysis revealed that formal technology assessment channels should be established to provide a voice for civil society to engage in policy making. Given the requirements and constraints, a feasible way to implement PTA seems to be the 'parliamentary office' model which would seem to be a good fit in the context of Ireland's current situation. Originality/value: The paper presents how PTA may be realised in a country without a formal PTA agency using a parliamentary office model to provide a channel for citizen engagement in STI policy making.